Cold, old, and metal-poor: new stellar substructures in the Milky Way's dwarf spheroidals - Lora, Verónica; Grebel, Eva K.; Schmeja, Stefan; Koch-Hansen, Andreas (The astrophysical journal, 2019)
Dwarf spheroidal galaxies (dSph) orbiting the Milky Way are complex objects often with complicated star formation histories and internal dynamics. In this work, we search for stellar substructures in four of the classical dSph satellites of the Milky Way: Sextans, Carina, Leo I, and Leo II. We apply two methods to search for stellar substructure: the minimum spanning tree method, which helps us find and quantify spatially connected structures, and the “brute-force” method, which is able to find elongated stellar substructures. We detected the previously known substructure in Sextans and also found a new stellar substructure within Sextans. Furthermore, we identified a new stellar substructure close to the core radius of the Carina dwarf galaxy. We report a detection of one substructure in Leo I and two in Leo II, but we note that we are dealing with a low number of stars in the samples used. Such old stellar substructures in dSphs could help us shed light on the nature of the dark matter halos, within which such structures form, evolve, and survive.